Creatinine-to-cystatin C ratio and all-cause and cardiovascular mortality in U.S. adults with nonalcoholic fatty liver disease: a nationwide cohort study - Chen, Yuanyuan; Yang, Bing; Chen, Huihui; Chen, Jun; Cao, Jinmin; Wang, Huijie; Chen, Chuantie (Frontiers in Nutrition, 2025)
BackgroundThe creatinine-to-cystatin C ratio (CCR) is an emerging marker of muscle mass, which influences the progression of nonalcoholic fatty liver disease (NAFLD). However, the relationship between CCR and long-term all-cause and cardiovascular mortality remains unclear in the US NAFLD population.MethodsThis nationally representative study analyzed data from the National Health and Nutrition Examination Survey (NHANES) 1999–2004, with mortality follow-up through December 31, 2019 via linkage to the National Death Index (NDI). NAFLD was determined using the Fatty Liver Index (FLI), while CCR was calculated as serum creatinine to cystatin C ratio. We employed multivariable Cox proportional hazards models to assess associations between CCR and mortality risk, expressed as hazard ratios (HRs) with 95% confidence intervals (CIs). The analytical approach included Kaplan–Meier survival analysis, restricted cubic spline regression for non-linear relationship assessment, and comprehensive subgroup and sensitivity analyses to evaluate result robustness.ResultsThis study included 3,897 participants with NAFLD (53.34% male, mean age 48.98 years), with 1,174 all-cause deaths and 333 cardiovascular deaths over a median follow-up of 206 months. CCR demonstrated significant inverse associations with both all-cause mortality (adjusted HR 0.83; 95% CI 0.78–0.88; p < 0.001) and cardiovascular mortality (adjusted HR 0.80; 95% CI 0.73–0.87; p < 0.001). In tertile analyses, higher CCR groups showed progressively lower risks, in Model 3(fully adjusted model): all-cause mortality: T2 = 0.65 (0.53, 0.79), T3 = 0.43 (0.32, 0.60), P for trend<0.001; cardiovascular mortality: T2 = 0.67 (0.50, 0.89), T3 = 0.34 (0.21, 0.53); P for trend<0.001. Restricted cubic spline analysis revealed an L-shaped association between CCR and all-cause mortality (turning point: 11.06), with each unit increase below 11.06 associated with a 36% risk reduction (HR 0.64; 95% CI 0.53–0.77; p < 0.001). In contrast, a linear relationship was observed for cardiovascular mortality (P for non-linearity = 0.972). Kaplan–Meier analysis confirmed superior survival rates in the highest CCR tertile for both endpoints (log-rank p < 0.001), with subgroup and sensitivity analyses affirming the robustness of these results.ConclusionIn this study of US adults with NAFLD, we identified a significant inverse association between CCR levels and risks of both all-cause and cardiovascular mortality. The stability of this association was confirmed through subgroup and sensitivity analyses, suggesting that CCR may play an important role in long-term prognosis among NAFLD patients.